Assessment of Cassava Peel Ash as a Partial Replacement of Cement in Plain Concrete Production. - Byamukama, Dan (Kabale University, 2023)
This work reports the outcome of an experiment carried out by using cassava peel ash (CPA) of varying quantities to partially replace cement in concrete work. The experiment was carried out by partially replacing cassava peel ash (CPA) of 0 to 20 percent by weight of cement at varying intervals of 2.5% and 5%. The percentage replacement used for this project was 0%, 2.5%, 5%, 7.5%, 10%, 12.5%, 15% and 20%. The concrete was batched with a mix of 1: 1.5:3. The cubes produced were allowed to cure for 7-28 days. Compressive strength test was conducted on the samples at 7, 21 and 28 days. Slump test and setting time of the concrete cubes were conducted. The result obtained showed that compressive strength of the concrete increased with increase in length of curing age, but decreased as the percentage of CPA increases. However, the strength still remained in the allowable range of workability for concrete in line with the British standard. CPA replacement of 2.5-7.5 percentages was found to be suitable considering the strength and safe use of the concrete. It was concluded that CPA replacement of 2.5%, 5%, 7.5% showed no significant loss in strength compared to the control sample and is stable and could be acceptable in most concrete works and other percentage replacements up to 20% can be used for light structures. At the long run cassava peeling that currently constitutes waste concern in south western Uganda can best be managed through alternative use.